Differential Effects of Munc18s on Multiple Degranulation-Relevant Trans-SNARE Complexes - Xu, Hao; Arnold, Matthew Grant; Kumar, Sushmitha Vijay (PLOS ONE, 2015)
Mast cell exocytosis, which includes compound degranulation and vesicle-associated piecemeal degranulation, requires multiple Q- and R- SNAREs. It is not clear how these SNAREs pair to form functional trans-SNARE complexes and how these trans-SNARE complexes are selectively regulated for fusion. Here we undertake a comprehensive examination of the capacity of two Q-SNARE subcomplexes (syntaxin3/SNAP-23 and syntaxin4/SNAP-23) to form fusogenic trans-SNARE complexes with each of the four granule-borne R-SNAREs (VAMP2, 3, 7, 8). We report the identification of at least six distinct trans-SNARE complexes under enhanced tethering conditions: i) VAMP2/syntaxin3/SNAP-23, ii) VAMP2/syntaxin4/SNAP-23, iii) VAMP3/syntaxin3/SNAP-23, iv) VAMP3/syntaxin4/SNAP-23, v) VAMP8/syntaxin3/SNAP-23, and vi) VAMP8/syntaxin4/SNAP-23. We show for the first time that Munc18a operates synergistically with SNAP-23-based non-neuronal SNARE complexes (i to iv) in lipid mixing, in contrast to Munc18b and c, which exhibit no positive effect on any SNARE combination tested. Pre-incubation with Munc18a renders the SNARE-dependent fusion reactions insensitive to the otherwise inhibitory R-SNARE cytoplasmic domains, suggesting a protective role of Munc18a for its cognate SNAREs. Our findings substantiate the recently discovered but unexpected requirement for Munc18a in mast cell exocytosis, and implicate post-translational modifications in Munc18b/c activation.